A study of enhanced ion formation from metal-semiconductor complexes in atmospheric pressure laser desorption/ionization mass spectrometry - Silina, Yuliya E.; Herbeck-Engel, Petra; Koch, Marcus (Journal of mass spectrometry, 2017)
The study of the key parameters impacted surface-assisted laser desorption/ionization-mass spectrometry is of broad interest. In previous studies, it has been shown that surface-assisted laser desorption/ionization-mass spectrometry is a complex process depending on multiple factors. In the presented study, we showed that neither porosity, light absorbance nor surface hydrophobicity alone influence the enhancement phenomena observed from the hybrid metal-semiconductor complexes versus individual targets, but small changes in the analyte attaching to the target significantly affect laser desorption ionization-efficiency. By means of Raman spectroscopy and scanning electron microscopy, it was revealed that the formation of an amorphous analyte layer after drying on a solid substrate was essential for the enhanced laser desorption ionization-signal observed from the hybrid metal-semiconductor targets, and the crystallization properties of the analyte appeared as a function of the substrate. Obtained results were used for the screening of regular and lactose-free milk samples through the hybrid metal-semiconductor target. Copyright © 2016 John Wiley & Sons, Ltd.